ANALYSIS OF ANTIOXIDANT PROTECTION STATE IN INFERTILE MEN OF DIFFERENT ETHNIC GROUPS - O. A. Vanteyeva; N. A. Kurashova; B. G. Dashiyev (Acta Biomedica Scientifica, 2013)
An important role in the pathogenesis of male infertility belongs activation of free radical oxidation. Intensification lipoperoxide processes occur together with a decrease in antioxidant protection. According to a study of two ethnic groups found that in men of reproductive age with Russian nationality infertility is most pronounced imbalance in the lipid peroxidation antioxidant protection compared to infertile men Buryat nationality. Reducing the concentration offat-soluble antioxidants (retinol, α-tocopherol) in the blood of Russian men with infertility say about the development of oxidative stress. In men, the Buryat nationality decreasing trend of antioxidant defense enzyme, primarily reduced the level of superoxide dismutase. Perhaps the decreased activity of superoxide dismutase in our study is related either to the depletion of its activity, or the inhibition of lipid peroxidation products. The increased level of lipid peroxidation is associated with a reduction in the antioxidant capacity of the system, which is unable to cope with overproduction of reactive oxygen species and, as a result, the processes of oxidative modification of lipids. The materials for biochemical studies were blood serum and red cells. The total antioxidant activity of serum and the content of its components (superoxide dismutase, α-tocopherol, retinol, blood-reduced glutathione, oxidized glutatione) were evaluated by a spectrofluorofotometer "SHIMADZU-1501" (Japan). Statistical analysis was performed by parametric tests. The study was supported by grants of the President of the Council of the Russian Federation (Scientific School 494.2012.7).